2009
DOI: 10.1250/ast.30.2
|View full text |Cite
|
Sign up to set email alerts
|

Principle and application of ball surface acoustic wave (SAW) sensor

Abstract: Detection of hydrogen gas is a crucial task for establishing safety and reliability of fuel cells, a key technology for the environment and our society. However, hydrogen is difficult to detect and various hydrogen sensors have many drawbacks. Here we report a novel hydrogen gas sensor, the ball surface acoustic wave (SAW) sensor, using Pd or PdNi sensitive film. The ball SAW sensor is based on a novel phenomenon, diffraction-free propagation of collimated beam along an equator of sphere. The resultant ultra-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Beyond these numbers, our experimental results showed that the nanowire sensors could be used effectively to measure concentrations on the order of ∼0.01%, close to the performance demonstrated by spherical sensors requiring sophisticated fabrication techniques [33]. In the same experiments, the thin film could actually be used for only about one order higher H 2 concentration.…”
Section: Saw -Sensorsupporting
confidence: 68%
“…Beyond these numbers, our experimental results showed that the nanowire sensors could be used effectively to measure concentrations on the order of ∼0.01%, close to the performance demonstrated by spherical sensors requiring sophisticated fabrication techniques [33]. In the same experiments, the thin film could actually be used for only about one order higher H 2 concentration.…”
Section: Saw -Sensorsupporting
confidence: 68%
“…[21][22][23] Pd is a hydrogen storage material, and therefore resistance increases when exposed to hydrogen because of the crystal lattice expansion of the crystal lattice by hydride formation. Surface acoustic wave sensors [24][25][26][27][28] are based on surface wave propagation caused by changes in electrical properties such as conductivity, permittivity, and carrier concentration. Thermoelectric sensors using a thermocouple device 29,30) detect heat generated by catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The phthalocyanine compounds absorb various chemical substances and are chemically stable. Therefore, phthalocyanine films have been utilized in gas sensors [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%